GLOBAL WARMING AND SMALL CYCLE: RISKS AND PROSPECTS - Dent, D.; Bai , Zh. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
Climate change is altering our understanding of ourselves, our society, the relationships between socio-economic and biophysical systems, and humanity's place on Earth. It is clear that the Earth is warming, but the scientific consensus for half a century has ignored the root cause of this threatening phenomenon, so the response has been ineffective and has not led to a consolidation of efforts. It is noted that the main reasons for the impact on the climate in the agro sector are the clearing of land for agriculture, the loss of year-round vegetation covering the soil, the reduction of forests, which expose the bare soil to solar radiation, creating tangible heat. The cooling effect of evaporation is limited or stopped by vegetation. This significantly changes formation and movement of moisture, stops rain from reaching deep into dry areas. In the article, the authors define the most important directions and some actions to solve the problem of bare soil surfaces. The earth still behaves as if it is trying to preserve the most favorable environment for all living things. It follows that the safest and most sustainable land use should imitate natural vegetation. Farmers and other land users should avoid exposing bare soil to direct sunlight. For this purpose, it is proposed to minimize tillage (no tillage) leaving the plow; to implement various crop rotations, preferably with perennial crops; to form a motley, diverse landscape that promotes a small water cycle in agroecosystems. The present research identifies only some of the processes through which a bare or non-bare landscape affects weather and climate. The work confirms that the impact of soil stripping from vegetation on atmospheric processes should be taken into account in the policy of regional land management in agro landscapes around the world, and even where significant land clearing for agricultural purposes is impossible.